The Influence of Self Help Groups on the Self Efficacy of People with Type 2 Diabetes Mellitus at the Paccerakkang Health Center in Makassar City - Syaipuddin; Suhartatik; Rahmawati; Sitti Nurbaya (Science Midwifery, 2022)
Optimal self-efficacy is a key factor in the success of self-management of DM patients. Poor self-efficacy affects many things, such as motivation and adherence, and can lead to poor self-care management by people affected by DM. Learning from the experiences of others through the law of self-help groups can increase self-efficacy.The purpose of this study was to clarify the influence of self-help groups on the self-efficacy of type 2 diabetes patients at the Paccerakkang Health Center in Makassar City. The design of this study was pre experimental and pre-test for one group. The free variable in this study is self-help group, and the bound variable in this study is self-efficacy. Sampling using simple random sampling method. The population includes all type 2 diabetics of the Paccerakkang Health Center in Makassar City, with a total sample of 3 respondents. Search for self-efficacy data using the DMSES (Diabestes Management Self Efficacy Scale) questionnaire. A statistical test by Wilcoxon signed the rating test. This research has been carried out in the Paccerakkang Health Center Working Area, Makassar City from June to July 2022. The population in this study were patients with Type 2 DM who visited data at the Paccerakkang Health Center in Makassar City, a sampling technique using Probability sampling with a simple random sampling type with a total sample of 46. The results of the research obtained were the influence of self-help groups with self-efficacy on patients with Type 2 DM at the Pacerakkang Health Center, Makassar City